Aspergillus spp. Isolated from Lungs of Poultry (Gallus gallus) at the Mycology Laboratory, School of Veterinary Medicine, Universidad Nacional, Heredia, Costa Rica between 2008 and 2021 and Associated Factors - Ulloa-Avellán, Óscar (2022)
Aspergillosis is a disease caused by some species of the fungus Aspergillus, occurring in both mammals (including humans) and birds, the latter being the most susceptible group. Aspergillus must be considered a public health concern as it affects the poultry industry economically and is an occupational risk to its workers. A retrospective study of fungal isolates from the lungs of chickens (Gallus gallus), analyzed between 2008 and 2021 at the Mycology Laboratory, School of Veterinary Medicine, Universidad Nacional, Heredia, Costa Rica was performed to report the prevalence of Aspergillus spp. in poultry farms in Costa Rica and their associated factors. A total of 1113 cases were received, of which 31% (n = 392; 95% CI: 28.3–33.7) were positive for fungal isolation. Aspergillus was the most frequently detected genus, and the most frequent sections were Fumigati (n = 197/392, 50.3%), Flavi (n = 90/392, 22.9%), and Nigri (n = 50/392, 12.7%). Significant effects (p < 0.05) related to the year, geographical origin, purpose, and age were identified in relation to the Aspergillus infection. The identified factors are explained by climatic variations in the tropics and the particularities of the birds. Future research including molecular characterization and antifungal susceptibility tests in animals, humans, and the environment, are needed to better understand the risks of the diseases caused by those fungi in this country.